THE IDEA OF NATURE: A COMPARATIVE STUDY BETWEEN R.G. COLLINGWOOD AND SEYYED HOSSEIN NASR - Kiran Latif (Journal of Religion and Society, 2025)
The work at hand explores the idea of nature from two standpoints; one hailing from the twentieth-century Western philosophy and expounded by the British Idealist R.G. Collingwood (d.1943) and the other from Perennialists among the contemporary Muslim tradition of philosophy as expounded by Seyyed Hossein Nasr (b.1933). Together, they are discussed to show the transformation of the perception of the idea of nature as the world met modernity in the twentieth-century. While R.G. Collingwood considers nature as part of human construct and hence bearing an immanent feature; Nasr on the other hand, attempts to interpret it through bestowing nature with its independent agency – one that is part of transcendental realities and acts on divine principles. The comparative analysis between two standpoints provided in this paper is relevant to the debate on conceptualizing the idea of nature in the wake of modern scientific interventions and the conservation of nature. It addresses the fundamental issue of mankind’s sustainable relationship with his environment – herein being referred to as nature. Keywords: Islam and Cosmology, Islam and metaphysics, Concept of Nature, History of ideas